Sustainable Food Security Hazards in Bangladesh & the Socio-Economic Impacts - Mizan, Md.Mizanur Rahman (International Journal of Sustainable Applied Sciences, 2023)
The major problem of Bangladesh are various circumstance frequently climate changing impacts and acute problem of geographical location. The unexpected converted to all important sector day by day it has extended. In present times the difficult right way management of pure drinking water, irrigation water supply and dumping management system. It is the problem of serious key factors of water wide arsenic. About 2.1 million respondents of our country has using tube wells which almost 55 ppb of arsenic contamination. The main reason of agricultural problem such as lack of adequate super seeds, insufficient fertilizers and others actors influence the negative prosecution of food security. If our country of all sectors balanced then frequently decrease negative impact factors. To be main focus point of defended food security and overall increasing the arable production which includes the major concern of government bodies, NGO'S and international organisation.